2010
DOI: 10.1200/jco.2009.26.8169
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Alterations Determine Clinical Subgroups and Survival of Patients With Choroid Plexus Tumors

Abstract: PURPOSE Choroid plexus carcinomas are pediatric tumors with poor survival rates and a strong, but poorly understood, association with Li-Fraumeni syndrome (LFS). Currently, with lack of biologic predictors, most children are treated with aggressive chemoradiation protocols. PATIENTS AND METHODS We established a multi-institutional tissue and clinical database, which enabled the analysis of specific alterations of the TP53 tumor suppressor and its modifiers in choroid plexus tumors (CPTs). We conducted high-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
143
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 200 publications
(153 citation statements)
references
References 25 publications
3
143
1
6
Order By: Relevance
“…Over 50% of CPC tumors carry somatic TP53 mutations, and TP53 mutant CPCs have been associated with increased genetic tumor instability and worse prognosis (5). Germline TP53 mutations have also been observed in patients with CPC as CPC is one of the hallmark cancers of the Li-Fraumeni syndrome (LFS), a familial cancer syndrome in which affected family members harbor a mutant copy of the TP53 tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over 50% of CPC tumors carry somatic TP53 mutations, and TP53 mutant CPCs have been associated with increased genetic tumor instability and worse prognosis (5). Germline TP53 mutations have also been observed in patients with CPC as CPC is one of the hallmark cancers of the Li-Fraumeni syndrome (LFS), a familial cancer syndrome in which affected family members harbor a mutant copy of the TP53 tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing of the coding region of TP53 (exons 2-11) was performed in the molecular diagnostic laboratory at The Hospital for Sick Children (Toronto) by direct Sanger sequencing of whole genome DNA as previously described (5).…”
Section: Tp53 Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) pathway is involved in ligand-induced apoptosis and was found to be methylated in a large proportion of CPPs [31]. In choroid plexus carcinomas, extensive analysis has shown that TP53 status can predict survival; those with wild-type TP53 and low total structural variation (TSV) have a favorable prognosis and do not require radiation therapy, while those with TP53-mutated tumors should be treated more aggressively [22]. Given the rarity of these lesions and complex molecular pathways involved in tumorigenesis, large multi-institutional collaborative efforts will be needed to produce meaningful progress in the treatment of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have demonstrated that these tumors can be safely removed, regardless of location, and likely do not require up-front radiation, even in cases of STR. Since some CPPs still recur despite GTR, future studies should build upon previously published genetic analysis of these tumors in order to identify markers that can refine our current grading scheme and provide improved insight towards predicting which tumors will recur [22][23][24][25][26]. Platelet-derived growth factor receptor (PDGFR) has been implicated in choroid plexus tumors, particularly carcinomas [27].…”
Section: Discussionmentioning
confidence: 99%